Ictal asystole as the first presentation of epilepsy: A case report and systematic literature review - Giada Giovannini (Epilepsy and Behavior Case Reports, 2014)
We report the case of a 69-year-old woman who presented with recurring episodes of mental confusion/dizziness followed by loss of consciousness, intense pallor, and sweating. Cardiologic investigations were unremarkable. The electroencephalogram recorded during one typical episode allowed the demonstration of a right frontotemporal seizure with progressive bradycardia leading to a 9-second asystole. Following levetiracetam treatment up to 2500 mg/day, seizures with ictal asystole (IA) recurred. An MRI compatible pacemaker was then implanted. At 26-month follow-up, the patient has not had further episodes of loss of consciousness. A systematic review (1950–Apr 2014) searching for cases in which IA was an early manifestation of epilepsy led to the observation of 31 cases. The time lag between the first seizures and the correct diagnosis of IA was long (average: 27 months; median: 12 months). Clinical history alone was not sufficient to prompt a correct diagnosis of IA, and only 11 out of 31 cases presented with symptoms suggestive of a seizure disorder. The majority of patients had a frontotemporal epilepsy with a slight prevalence of left-side involvement (19 out of 31). Ictal bradycardia–asystole is an important condition that should be recognized by epileptologists, neurologists, as well as emergency department physicians. It is important to underscore that IA not only can occur in patients with drug-resistant epilepsy but also may be the first manifestation of the patient's epilepsy.